Avaliação das dificuldades alimentares e mastigatórias e sinais e sintomas de bruxismo em crianças com Síndrome de Down - Miyagui, Sânia Aparecida [UNIFESP] (2023)
Down Syndrome is a condition associated to particular and specific characteristics regarding oral health and growth of orofacial structures that can directly affect dietary, nutritional and masticatory aspects. The objective of the study was to evaluate the oral and nutritional clinical characteristics, feeding and masticatory difficulties, as well as signs and symptoms of bruxism in 100 individuals with Down Syndrome aged between five and 18 years (median=12 years). According to the medical history, 59% of the participants did not have chronic diseases, while 14% had thyroid gland dysfunction and 17% had cardiovascular diseases. Delays in the chronology of eruption of permanent teeth were observed, in addition to a higher frequency of Class III molar relationship in the permanent dentition. The mean index of decayed, missing (or exfoliated) and filled teeth (dmf/DMFT) was higher according to the stage of dentition, being equal to 1.1 in the deciduous dentition and 2.5 in the permanent dentition; at 14-18 years old caries experience was 82%. Frequencies of bleeding on inspection and periodontal pockets were found in 26.5% and 10% of participants in the mixed dentition, and 77% and 45.5% in the permanent dentition, respectively. The frequencies of visible biofilm and reported teeth grinding/clenching were found to be 97-100% and 70-82% in the three dentitions. As for nutritional and dietary aspects, the frequency of children with excess weight (overweight, preobesity and obesity) increased according to age, being 39% in the age range of 5-7 years and 54% in the range of 14-18 years; 30% of the participants did not receive natural breastfeeding and the average time of bottle feeding was 29.7 months. The consumption of fresh fruit had a median=5 (every day) in all age groups, although the intake of juices, soft drinks and sausages was high and the consumption of sweets and biscuits increased with age. According to parents, most participants were classified as having no feeding difficulties (87%) and only eight children were classified as having moderate to severe difficulties. Masticatory difficulties were more frequent in the age group of 8-10 years, corresponding to the mixed dentition. Comparing with literature data obtained in typical children, delays in tooth eruption, higher frequency of Molar Class III, high levels of visible biofilm and teeth grinding or clenching were observed in children and adolescents with Down Syndrome. Furthermore, the high consumption of sweets and processed foods, the longer duration of bottle feeding and the frequency of overweight observed indicate the high risk of caries, cardiovascular and metabolic diseases to which this population is exposed.